Comparative analysis of prostate‐specific antigen by two‐dimensional gel electrophoresis and capillary electrophoresis. Issue 3 (24th October 2016) - Barrabés, Sílvia; Farina‐Gomez, Noemi; Llop, Esther; Puerta, Angel; Diez‐Masa, Jose Carlos; Perry, Antoinette; de Llorens, Rafael; de Frutos, Mercedes; Peracaula, Rosa
Abstract : Serum levels of Prostate‐Specific Antigen (PSA) are not fully specific for prostate cancer (PCa) diagnosis and several efforts are focused on searching to improve PCa markers through the study of PSA subforms that could be cancer associated. We have previously reported by 2DE a decrease in the sialic acid content of PSA from PCa compared to benign prostatic hyperplasia patients based on the different proportion of the PSA spots. However, faster and more quantitative techniques, easier to automate than 2DE, are desirable. In this study, we examined the potential of CE for resolving PSA subforms in different samples and compared the results with those obtained by 2DE. We first fractionated by OFFGEL the subforms of PSA from seminal plasma according to their p I s and analyzed each separated fraction by 2DE and CE. We also analyzed PSA and high p I PSA, both from seminal plasma, and PSA from urine of a PCa patient. These samples with different PSA spots proportions by 2DE, due to different posttranslational modifications, also presented different CE profiles. This study shows that CE is a useful and complementary technique to 2DE for analyzing samples with different PSA subforms, which is of high clinical interest.